Limited evidence of a shared genetic relationship between C-reactive protein levels and cognitive function in older UK adults of European ancestry - Packer, Amy; Corbett, Anne; Arathimos, Ryan; Ballard, Clive; Aarsland, Dag; Hampshire, Adam; Dima, Danai; Creese, Byron; Malanchini, Margherita; Powell, Timothy R. (Frontiers in Dementia, 2023)
Introduction Previous studies have shown associations between cognitive function and C-reactive protein (CRP) levels in older adults. Few studies have considered the extent to which a genetic predisposition for higher CRP levels contributes to this association. Methods Data was analyzed from 7,817 UK participants aged >50 years as part of the PROTECT study, within which adults without dementia completed a comprehensive neuropsychological battery. We constructed a polygenic risk score (PRS-CRP) that explained 9.61% of the variance in serum CRP levels (p = 2.362 × 10−7) in an independent cohort. Regressions were used to explore the relationship between PRS-CRP and cognitive outcomes. Results We found no significant associations between PRS-CRP and any cognitive measures in the sample overall. In older participants (>62 years), we observed a significant positive association between PRS-CRP and self-ordered search score (i.e., spatial working memory). Conclusion Whilst our results indicate a weak positive relationship between PRS-CRP and spatial working memory that is specific to older adults, overall, there appears to be no strong effects of PRS-CRP on cognitive function.